FAKTOR – FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK DAERAH PROVINSI JAWA TENGAH 2014 - 2018 - Putra, Anggi Priandita; Harimurti, Fadjar; Sunarti, Sunarti (Universitas Slamet Riyadi, 2021)
The purpose of this study is to determine the effect of inflation, GrossRegional Domestic Product, Total Population on Regional Tax Revenues ofCentral Java Province 2014 - 2018. This study uses a sample type ofnonprobability sampling used in this study is saturated sampling or often called acensus, then The sample in this study is all of the population used in this study asmany as 35 which are all districts and cities in Central Java Province consistingof 29 districts and 6 cities using the Stakeholder theory. The type of data used inthis study is secondary data. The results of this study indicate that the significancevalue of inflation is 0.880 > 0.05, it can be explained that inflation has no effecton local tax revenues. The significance value of Gross Regional Domestic Product(PDRB) is 0.000 <0.05, it can be explained that the GRDP has a significant effecton Regional Tax Revenue. The significance value of Total Population is 0.000<0.05, it can be explained that Total Population has a significant effect on LocalTax Revenue. The results of the Determination Coefficient show an Adjusted RSquare of 0.635, the effect of the independent variable, namely inflation, GrossRegional Domestic Product (GRDP) and Total Population on Local Tax Revenuesby 64%, while the rest (100% - 64%) = 36% is influenced by other variables notresearched.